Pre-directional appliance: A new approach to correct shifted premaxilla in bilateral cleft cases - P S Daigavane; P Hazarey; R Vasant; R Thombare (Wolters Kluwer Medknow Publications, 2011)
Management of bilateral cleft lip and palate cases is a challenging task, and if the premaxilla is shifted to either side, it poses a problem for the surgeon to operate and also for the orthodontist to do the orthodontic alignment. The aim of this study was to reposition the shifted premaxilla for better retraction with presurgical infant orthopedics, thus reducing the tissue tension and further scarring which have detrimental effects on maxillary growth. The innovative technique with pre-directional (PD) appliance is easy to fabricate and use and works in this direction. Acrylic, springs, permasoft liner, elastics, retentive tapes. Previous approach for the shifted premaxilla was more focused on the surgical correction. In adults, surgery with osteotomy is the only option, with its own limitations and disadvantages, in repositioning the shifted premaxilla. Thus, PD appliance aids to correct the shifted premaxilla in presurgical molding stage. The premaxilla was thus shifted 5.5 mm to the left side, with premaxilla in facial symmetry, with the PD appliance. Presurgical orthopedics with PD appliance is worth in infants with shifted premaxilla in bilateral clefts cases.